Current trends and current problems of training educational managers - Tsekhmister, Ya.; Malatsai, I.; Nechitailo, I. S.; Нечітайло, І. С.; ORCID: https://orcid.org/0000-0002-0656-0370; Yemelyanova, O.; Korol, O.; Statsenko, N. (Фінансово-кредитна діяльність: проблеми теорії і практики. – 2021. – Т. 6 (41). – С. 556-563, 2021)
Проаналізовано проблему професійної підготовки фахівців у сфері освітнього менеджменту. Виявлено, що поява зазначеної спеціальності зумовлена метаморфозами в суспільно-економічному житті та гострою конкуренцією між освітніми установами. Окреслено такі ключові проблеми освітнього менеджменту: практична діяльність керівника, упровадження інновацій; процес підготовки фахівців; моніторинг ефективності та оцінка якості освітнього менеджменту. З’ясовано, що освітній менеджмент — міждисциплінарна категорія, котра перебуває на периферії теорії і практики освітньої галузі та економіки. І якщо в першому варіанті зв’язок очевидний, то у другому — на перший погляд латентний, проте саме суспільно-економічні процеси детермінують діяльність керівника, завдання якого полягає у вивченні тенденцій ринку праці та побудові ефективної стратегії загального розвитку закладу освіти. Актуальним питанням є висвітлення базових для керівника особистісних якостей, психологічних характеристик і практичних умінь. Так, чільне місце займає вивчення когнітивної сфери, творчого потенціалу та готовності до інноваційної діяльності. Злободенною залишається і проблема організації освітнього процесу. Зокрема, компетентнісного підходу і розкриття творчих можливостей студентів як ресурсу для майбутньої професійної діяльності. Глибше розуміння професійної підготовки забезпечив фрагментарний аналіз окремих аспектів діяльності закладів вищої освіти в Україні, Великій Британії та Сполучених Штатах Америки (по одному закладу із кожного регіону). Встановлено, що загальні тенденції підготовки аналогічні, проте європейські ЗВО акцентують увагу на міжнародній академічній мобільності; США — на практичній компоненті; України — теоретичній базі. Розроблено ієрархічну модель факторів детермінантів освітнього процесу підготовки освітніх менеджерів.

The article analyzes the problem of professional training in the field of educational management. It was found that the emergence of this specialty is due to metamorphoses in socio-economic life and fierce competition between educational institutions. Given the number of multi-vector scientific publications, this problem is relevant and dynamic, so the field for its disclosure provides new research directions. The review of the literature allowed to outline the following key problems of educational management: practical activities of the head, the introduction of innovations; the process of training specialists; monitoring the effectiveness and evaluation of the quality of educational management. Through acquaintance and analysis with them, we made an attempt to reveal current trends and current issues of training education managers. Educational management has been found to be an interdisciplinary category on the periphery of education and economics. And if in the first case the connection is obvious, in the second - at first glance latent, but it is socio-economic processes that determine the activities of the head, whose task is to study labor market trends and build an effective strategy for the overall development of education. The topical issue is the coverage of basic personal qualities, psychological characteristics and practical skills. Thus, the study of cognitive sphere, creative potential and readiness for innovative activity occupies a prominent place. The problem of organizing the educational process also remains topical. In particular, the competence approach and the disclosure of creative opportunities of students as a resource for future professional activities. A deeper understanding of professional training was provided by a fragmentary analysis of certain aspects of higher education institutions in Ukraine, the United Kingdom and the United States (one institution from each region). It is established that the general trends in training are similar, but European universities focus on international academic mobility; USA — on the practical component; Ukraine — the theoretical basis. Based on the above material, we have developed a hierarchical model of determinants of the educational process of training educational managers. They determined that their impact, depending on the scale of the action — only on education or on society as a whole, can be explicit or latent. This model gives a clear idea of the place of educational management in public life. We see the prospects for further research in the development of specific recommendations for solving current problems of training education managers.

Проанализирована проблема профессиональной подготовки специалистов в сфере образовательного менеджмента. Выявлено, что появление указанной специальности обусловлено метаморфозами общественно-экономической жизни и острой конкуренцией между образовательными учреждениями. Обозначены следующие ключевые проблемы образовательного менеджмента: практическая деятельность руководителя, внедрение инноваций; процесс подготовки профессионалов; мониторинг эффективности и оценка качества образовательного менеджмента.
Сучасні тенденції та актуальні проблеми підготовки менеджерів освіти
Tsekhmister, Ya. Current trends and current problems of training educational managers / Tsekhmister Ya., Malatsai I., Nechitailo I. and ot. // Фінансово-кредитна діяльність: проблеми теорії і практики. – 2021. – Т. 6 (41). – С. 556-563.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; заклад вищої освіти; higher education institution; высшее учебное заведение; професійна підготовка; professional training; профессиональная подготовка; освітній менеджмент; educational management; образовательный менеджмент; лідерство; leadership; лидерство; освітній процес; educational process; учебный процесс; керівник; manager; менеджер освіти; інновації; innovation; инновации